(untitled) (Al-Farooq Journal of Sciences, 2026)
This study aimed to identify the role of sustainable education in building environmental citizenship among pupils in the first cycle of basic education in schools of Zawiya Al-Gharb Municipality. The study adopted the descriptive-analytical method and used a questionnaire to collect data from a sample of 120 participants, including 100 pupils and 20 teachers. The results showed high levels of sustainable education availability, environmental citizenship, and the contribution of sustainable education to building it. Statistically significant differences were found in favor of teachers and according to school and grade level in some dimensions, while no differences appeared by gender or years of experience.